Effect of heat diffusion during state transitions in resistive switching memory device based on nickel-rich nickel oxide film - Hu, S. G. (2013)
The switching behaviors of the resistive switching device based on Ni-rich nickel oxide thin film during the set and reset processes in the pulse voltage experiment have been examined. In the switching from a high-resistance state (HRS) to a low-resistance state (LRS) during the set process, the formation of filament is the dominant process. The switching is easier to occur with a shorter off time between pulses, indicating that heat diffusion plays an important role. On the other hand, in the switching from the LRS to the HRS during the reset process, there is a competition between the formation and deformation of filament, which is much stronger than that in the set process. The heat diffusion during the off time between pulses affects both the formation and deformation of filaments. Thus, there is no definite relationship in statistics between the off time and the occurrence of the reset switching.